Effect of competition on stress salivary biomarkers in elite and amateur female adolescent inline skaters - Dehghan, F.; Khodaei, F.; Afshar, L.; Shojaei, F. K.; Poorhakimi, E.; Soori, R.; Fatolahi, H.; Azarbayjani, M. A. (Science & Sports, 2019)
Objectives: The purpose of the present study was to investigate the effect of competition on stress salivary biomarkers alpha-amylase (sAA), cortisol, and dehydroepiandrosterone (DHEA) in elite or amateur female adolescent inline skaters. Material and methods: Eighteen female adolescent inline skaters (9 elites and 9 amateurs) who have competed in official skate competitions, participated in the present study. Unstimulated whole saliva was collected during their rest day, 1h and immediately before competition (pre-competition), as well as immediately and 1h after the competition (post-competition). Free cortisol, sAA, DHEA, and total protein concentrations were assessed. Results: Cortisol concentrations of elite group significantly increased 1h before and pre-competition compared to rest day (P<0.05) whereas no significant changes observed in amateur group (P>0.05). The sAA concentrations were significantly higher in the elite group at 1h before and at pre-competition compared to the rest day (P<0.05). sAA concentrations of amateur group were significantly higher at pre-competition, post-competition, and 1h after competition compared to the rest day (P<0.05). DHEA levels of both groups markedly decreased 1h after competition compared to the rest day (P<0.05). No significant differences in DHEA concentrations were observed between the two groups (P>0.05). The ratio of DHEA to cortisol exhibited significant difference among the five measurement stages in the amateur group (P<0.05), whereas no significant changes in this ratio were observed in the elite group (P>0.05). The total protein concentrations of the elite group increased significantly during three stages, pre-competition, post-competition, and 1h after competition compared to rest day (P<0.05). Additionally, the total protein concentrations at pre-competition and 1h after competition were significantly higher in elite group (P<0.05). Conclusion: Our results confirmed that the optimum increase in adrenal activity occurs before a competition, which can improve athletic performance. However, a similar increase after a competition suggests the body's attempt to maintain homeostasis. Therefore, anticipatory stress indicates that athletes need to relax before a competition.